For Whom the Bell Tolls (and Nods): Spit-acular Saliva - Shaw, Dana K; Kotsyfakis, Michail; Pedra, Joao H F (Current tropical medicine reports, 2016)
Having emerged during the early part of the Cretaceous period, ticks are an ancient group of hematophagous ectoparasites with significant veterinary and public health importance worldwide. The success of their life strategy can be attributed, in part, to saliva. As we enter into a scientific era where the collection of massive data sets and structures for biological application is possible, we suggest that understanding the molecular mechanisms that govern the life cycle of ticks is within grasp. With this in mind, we discuss what is currently known regarding the manipulation of Toll-like (TLR) and Nod-like (NLR) receptor signaling pathways by tick salivary proteins, and how these molecules impact pathogen transmission.
Keywords: Innate immune signaling; Tick-borne diseases; Toll-like receptors (TLR); Nod-like receptors (NLR); Tick saliva